Wewenang Lembaga Perkreditan Desa Dalam Hal Pemberian Kredit Dengan Jaminan Hak Tanggungan - Setiawan, I Putu Yudhi; Yustiawan, Dewa Gede Pradnya (Acta Comitas; Vol 8 No 03 (2023), 2023)
The purpose of the research is to understand the authority of village credit institutions in terms of granting credit with mortgage rights as collateral and the legal strength of credit agreements with land ownership guarantees at village credit institutions. The research uses normative research methods, because the focus of the study starts from the blurring of norms. This ambiguity in norms occurs because the rules governing the binding of collateral for credit agreements are unclear, especially regarding collateral for land ownership rights at village credit institutions. This research approach is a statutory approach, a conceptual approach. The analysis used on this data is only normative-qualitative analysis. The results of this research are that LPDs are not authorized as legal subjects of mortgage rights, LPDs are due (owned) by traditional villages in Bali whose existence is recognized based on customary law through the provisions of the LKM Law. LPD can still distribute credit with collateral for land rights using a private deed with the debtor while still prioritizing the principle of prudence and not conflicting with local traditional village awig-awig. Credit agreements and collateral agreements made by LPD under their control remain valid and have binding legal force just like the law for the parties who make them as long as they fulfill the conditions for the validity of the agreement, namely subjective conditions and objective conditions. LPD as a financial institution that provides credit facilities to debtors legally executes collateral which becomes credit collateral at LPD if the debtor does not meet its achievements.